The Role of Renewable and Nonrenewable Energy on Agricultural Economics in Indonesia - Nendissa, Doppy Roy; Iriany, Atiek; Sui, Jeky Melkianus; Khoiriyah, Nikmatul; Suphattanakul, Onuma; Wisetsri, Worakamol (International Journal of Energy Economics and Policy, 2022)
Recently, the prominent involvement of energy in the agriculture sector significantly influences agriculture economics and needs researchers’ focus. Hence, the current article examines the impact of renewable energy production (REP) and consumption, fossil fuel energy consumption (FFEC) and energy import and use on the agriculture economics in Indonesia. The researchers have followed the secondary source of data collection, such as world development indicators (WDI) and extracted data from 1986 to 2020. The current research has used the Augmented Dickey-Fuller (ADF) test for checking the unit root and autoregressive distributed lag (ARDL) to test the nexus among constructs. The results revealed that renewable energy production and consumption, fossil fuel energy consumption and energy import and use have a positive association with agriculture economics in Indonesia. This study provides guidelines to the policymakers while developing regulations related to the improvement of agriculture economics.